STRATEGI PERPUSTAKAAN MENERAPKAN LITERASI UNTUK MENINGKATKAN IMAJINASI, KREATIVITAS, INOVASI - Laksmi Laksmi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
This research discusses the library strategy of applying literacy to increase imagination, creativity and innovation. Various libraries carry out various literacy programs, including GLN and GLS. However, the results have not looked encouraging. UNESCO in 2017 stated that out of a total of 61 countries, Indonesia ranked 60th at a low literacy level. Literacy activities, namely activities that empower the movement of reading and writing, can make someone create imagination, creativity, and innovation. Libraries must have effective and efficient literacy implementation strategies, based on 6 types of literacy, namely literacy, numeracy literacy, scientific literacy, ICT literacy, financial literacy, and cultural and citizenship literacy. Librarians need to pay attention to the process of developing literacy, namely: text and facilities; literacy type and purpose, learning context, and learner character. Librarians determine the competencies to be achieved, then determine the quality of character and type of literacy. In the application process, librarians introduce methods of reading books and storytelling, creating a safe and pleasant atmosphere, letting users experiment, and playing roles.